THE EFFECT OF BRAND AWARENESS AND BRAND IMAGE ON CUSTOMER DECISIONS IN USING GOLD PAWN SERVICES AT ACEH SHARIA BANK WITH CUSTOMER TRUST AS A VARIABLE MEDIATION - Teuku Muhammad Azani; Herman Fithra; Adnan (RADJA PUBLIKA, 2024)
Gold pawning transactions in Indonesia are currently growing rapidly, both managed by Islamic banking and non-Islamic banking, including non-bank financing institutions. One of the banks holding a gold pawnshop program is Bank Aceh Syariah. The Rahn principle operated by Bank Aceh Syariah uses the Al-qard and Alijarah contracts, namely by renting a safe deposit box (SDB) as a place to store gold, the customer will be charged administrative costs and also the cost of using SDB, and this concept is used by Bank Aceh Syariah Lhokseumawe Branch to provide lower fees to customers compared to other financial institutions and pawnshops. The purpose of this study was to examine the effect of brand awareness and brand image on brand trust and customer decisions in using gold pawn products at Bank Aceh Syariah Lhokseumawe Branch. The sample in this study were 150 customers of gold pawning products. The data used is primary data collected through questionnaires distributed via Google form. The data analysis method uses Structural Equation Modeling (SEM) and the Analysis of Moment Structure (Amos) tool. The results showed that brand awareness had a positive and significant effect on brand trust and customer decisions to buy Rahn Bank Aceh Syariah products. Furthermore, brand image was found to have a positive and significant effect on brand trust and customer purchasing decisions. Then brand trust has a positive and significant effect on customer purchasing decisions. In testing the indirect effect, it was found that the brand trust variable was found to mediate the influence of brand awareness and brand image on the customer's purchasing decision for gold pawning products, Bank Aceh Syariah, Lhokseumawe Branch. The results of this research are expected to provide important information for bank managers in developing strategies and planning for banking business, especially gold pawning products.